Adsorption Isotherms of Some Non-Steroidal Drugs on Single Wall Carbon Nanotube - Vadi, Mehdi (Asian Journal of Chemistry, 2013)
The objective of this work was to study the adsorption behaviour of non-steroidal antiinflammatory drugs (NSAIDs) e.g., aspirin, diclofenac and naproxen by single walled carbon nanotube as the function of initial concentration of adsorbate through adsorption isotherms. The amount of NSAIDs adsorbed from aqueous solution increases with the increase of the initial NSAIDs concentration. The adsorbent capacity was determined using the parameters of Langmuir, Freundlich and Temkin adsorption isotherm models that the NSAIDs adsorption isotherm data fit best to the Freundlich isotherm model. The results showed that aspirin has maximum adsorption rate of single wall carbon nanotube.